0
$\begingroup$

Consider a discrete analog to the Poisson process. Let the sequence $X_i$ be independent geometrically (with parameter $p$) distributed random variables that signify the inter arrival times of events. Let $S_k$ be the sequence of times at which the $k$th event occurs, ie. the renewal times. $S_k = X_1 + \ldots + X_k$ so that $S_k$ has a negative binomial distribution with parameters $k$ and $p$.

Now consider the joint distribution of two consecutive renewal times.

How do you show that: $P(S_k \leq n ; S_{k+1} = n+j) = P(S_{k+1} = n+1)(1-p)^{j-1}$ for $n \geq k$?

$\endgroup$
1
$\begingroup$

Let $Q_{k,n}$ be the probability that the first $k$ events occur by time $n$ (i.e., $S_k \le n$) and event $k+1$ does not occur by time $n$ (i.e., $S_{k+1} > n$). Then $$ P(S_k\le n ; S_{k+1}=n+j) = p(1-p)^{j-1} Q_{k,n}, $$ since the probability of $j-1$ consecutive non-events (at times $n+1,n+2,...,n+j-1$) followed by a single event is $p(1-p)^{j-1}$, while $$ P(S_{k+1}=n+1) = p Q_{k,n}. $$ The desired equality follows.

$\endgroup$
0
$\begingroup$

\begin{align*} P(S_k \le n, S_{k+1} = n+j) &= \sum_{\nu = k}^n P(S_k = \nu, S_{k+1} = k+j)\\\ &= \sum_{\nu = k}^n P(S_k = \nu, X_{k+1} = n+j-\nu)\\\ &= \sum_{\nu = k}^n P(S_k = \nu)P(X_{k+1} = n+j-\nu)\\\ &= \sum_{\nu = k}^n P(S_k = \nu)(1-p)^{n+j-\nu -1}p\\\ &= (1-p)^{j-1}\sum_{\nu = k}^n P(S_k = \nu)(1-p)^{n-\nu}p\\\ &= (1-p)^{j-1}\sum_{\nu = k}^n P(S_k = \nu)P(X_{k+1} = n+1-\nu)\\\ &= (1-p)^{j-1}\sum_{\nu = k}^n P(S_k = \nu, X_{k+1} = n+1-\nu)\\\ &= (1-p)^{j-1} P(S_k \le n, S_{k+1} = n+1)\\\ &= (1-p)^{j-1} P(S_{k+1} = n+1). \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.